Global gene expression and morphological alterations in the mammary gland after gestational exposure to bisphenol A, genistein and indole-3-carbinol in female Sprague-Dawley offspring - Grassi, Tony F. [UNESP] (2016)
This study aimed to evaluate the modifying effects of dietary genistein (GEN) and indole-3-carbinol (I3C) on early mammary gland development in female Sprague-Dawley offspring born to mothers exposed to BPA during gestation. Pregnant rats were treated with BPA25 or 250 μg/kg bw/day from gestational days 10 to 21 with or without dietary intake of GEN (250 mg/kg chow) or I3C (2000 mg/kg chow). At post-natal day (PND) 21, female offspring fromdifferent litterswere euthanized for mammary gland development and gene expression analyses. Our results indicated that prenatal exposure to BPA25 and 250 did not modify the ductal elongation of the mammary gland tree or the estrogen receptor alpha (ER-a) expression in terminal end buds (TEBs). However, BPA25- exposed offspring had a higher number of terminal structures (TEBs + TDs) and an increased mammary branching and cell proliferation index in TEBs. Besides that, BPA25 and 250 modulated the expression of several genes in the immature mammary gland that were not changed in a dose dependent manner and involved different clusters of up- and down-regulated genes. Furthermore, BPA25 and BPA250+I3C-treated groups also had a higher number of enriched functional gene categories. In addition, maternal dietary GEN and I3C in association with BPA exposure produced specific gene expression alterations in the mammary gland and overcome the adverse effect of BPA25, decreasing the branching of the mammary gland. In conclusion, prenatal BPA exposure induced both morphological and gene expression modifications on the mammary gland that dietary intake of GEN and I3C reverted on BPA25-exposed animals.